2014
DOI: 10.1136/archdischild-2013-305720
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual variation in midazolam clearance in children

Abstract: ObjectivesTo determine the extent of inter-individual variation in clearance of midazolam in children and establish which factors are responsible for this variation.MethodsA systematic literature review was performed to identify papers describing the clearance of midazolam in children. The following databases were searched: Medline, Embase, International Pharmaceutical Abstracts, CINAHL and Cochrane Library. From the papers, the range in plasma clearance and the coefficient of variation (CV) in plasma clearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
(86 reference statements)
0
16
0
Order By: Relevance
“…Vertical error bars represent the total range of reported clearances or, in the case of one study, the 95% confidence interval. Literature data were obtained after a search of PubMed, with keywords including midazolam, clearance, paediatric, children and pharmacokinetics, and additional studies were identified from reviews and summarizing studies . Studies published up to 25 years ago were included if paediatric subjects in the study received intravenously administered midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Vertical error bars represent the total range of reported clearances or, in the case of one study, the 95% confidence interval. Literature data were obtained after a search of PubMed, with keywords including midazolam, clearance, paediatric, children and pharmacokinetics, and additional studies were identified from reviews and summarizing studies . Studies published up to 25 years ago were included if paediatric subjects in the study received intravenously administered midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the sedation strategy for a patient with severe sepsis should take into account that critical illness reduces midazolam clearance independently of serum creatinine levels and could increase sedation depth. Critical illness thus leads to a great variability in midazolam clearance, as was confirmed in a systematic review . It should be clear that this variability greatly affects correct dosing.…”
Section: Pharmacological Agentsmentioning
confidence: 79%
“…However, sedative drugs sometimes have several undesirable effects, including respiratory depression, hypotension, seizure-like activity, and paradoxical reactions [18,19]. Moreover, it is difficult to determine the effective dosage because children have a narrow safety margin and a large variation among sedative drugs [6]. According to previous studies, a combined therapy with nonpharmacological and pharmacological interventions was more effective than medication alone [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Third, parents should also wear surgical suits, which may be not effective in reducing children's anxiety. The use of sedative drugs can be an effective way to reduce children's anxiety, but it is difficult to determine the effective dosage because children have a narrow safety margin and a large variation among sedative drugs [6]. Thus, several studies have been conducted to reduce anxiety in children by nonpharmacological methods.…”
Section: Introductionmentioning
confidence: 99%